2004
DOI: 10.1111/j.1365-2265.2004.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of chylomicrons in patients with congenital lipoatrophic diabetes: a study with emulsion models of chylomicrons

Abstract: The metabolism of chylomicrons tested by the emulsion method is impaired in lipoatrophic diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition, the results indicate that these atherogenic effects may be modulated by the presence of common dietary oxysterols in the remnant particles. These mechanisms, therefore, are likely to contribute to the increased risk of the development of atherosclerotic lesions in subjects with relatively common conditions, such as diabetes mellitus and obesity, where clearance of chylomicron remnants from the circulation is delayed [35,51–53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results indicate that these atherogenic effects may be modulated by the presence of common dietary oxysterols in the remnant particles. These mechanisms, therefore, are likely to contribute to the increased risk of the development of atherosclerotic lesions in subjects with relatively common conditions, such as diabetes mellitus and obesity, where clearance of chylomicron remnants from the circulation is delayed [35,51–53].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests defective activity of lipoprotein lipase (LPL), and indeed protease inhibitor therapy has been associated with low levels of postheparin plasma LPL activity [49,50] and decreased expression of LPL in subcutaneous adipose tissue [51]. Similarly, the impaired removal of chylomicron remnants has been reported in six CGL patients with diabetes [52 ]. Five of the six patients had decreased plasma LPL activity.…”
Section: Lipid Kinetics In Lipodystrophy Syndromesmentioning
confidence: 95%
“…For instance, in a 25-year-old patient with BSCL, the ability of insulin to inhibit lipolysis was markedly blunted [27]. In six patients with BSCL, the postprandial lipid metabolism evaluated using labeled TG-rich lipoprotein (TRL) emulsion revealed that both lipoprotein lipase (LPL)-mediated lipolysis and removal of TRL remnant were impaired and delayed [28]. The data on LPL activity are quite variable since in some reports LPL activity was reported to be normal [29,30], whereas it was markedly reduced in other cases [31].…”
Section: Clinical Characteristics Of Dyslipidemia In Inherited Lipodymentioning
confidence: 99%